Panax Notoginseng Saponins Attenuate Myocardial Ischemia-Reperfusion Injury Through the HIF-1α/BNIP3 Pathway of Autophagy. Issue 2 (February 2019) - Liu, Xin-Wen; Lu, Meng-Kai; Zhong, Hui-Ting; Wang, Li-Hong; Fu, Yong-Ping
Abstract : Background and Objective: Panax Notoginseng Saponins (PNS) is a formula of Chinese medicine commonly used for treating ischemia myocardial in China. However, its mechanism of action is yet unclear. This study investigated the effect and the mechanism of PNS on myocardial ischemia-reperfusion injury (MIRI) through the hypoxia-inducible factor 1α (HIF-1α)/bcl-2/adenovirus E1B19kDa-interacting protein3 (BNIP3) pathway of autophagy. Methods: We constructed a rat model of myocardial injury and compared among 4 groups (n = 10, each): the sham-operated group (Sham), the ischemia-reperfusion group (IR), the PNS low-dose group, and the PNS high-dose group were pretreated with PNS (30 and 60 mg/kg, respectively). Serum creatine kinase, malonaldehyde (MDA), lactate dehydrogenase, myocardial tissue superoxide dismutase, and reactive oxygen species were detected in rats with myocardial ischemia-reperfusion after the intervention of PNS. The rat myocardial tissue was examined using hematoxylin and eosin (H&E) staining, and the mitochondria of myocardial cells were observed using transmission electron microscopy. The expressions of microtubule-associated protein light chain 3 (LC3), HIF-1α, BNIP3, Beclin-1, and autophagy-related gene-5 (Atg5) in rat myocardial tissue were detected using Western blotting. Results: The results showed that PNS was significantly protected against MIRI, as evidenced by the decreasing in the concentration of serum CK, MDA, lactate dehydrogenase, and myocardial tissue superoxide dismutase, reactive oxygen species, the attenuation of myocardial tissue histopathological changes and the mitochondrial damages of myocardial cells, and the increase of mitochondria autophagosome in myocardial cells. In addition, PNS significantly increased the expression of LC3 and the ratio of LC3II/LC3I in rat myocardial tissue. Moreover, PNS significantly increased the expression of HIF-1α, BNIP3, Atg5, and Beclin-1 in rat myocardial tissue. Conclusions: The protective effect of PNS on MIRI was mainly due to its ability to enhance the mitochondrial autophagy of myocardial tissue through the HIF-1α/BNIP3 pathway. Abstract : Supplemental Digital Content is Available in the Text.